Effective treatment of acute graft-versus-host disease following liver transplantation using an integrated regimen centered on antithymocyte globulin: a single-center experience - Zheng, Qiming; Zhang, Li; Wang, Honghai; Abdisamat, Ababakri; Wang, Xiaodong; Xiao, Xia; Jiang, Wentao (Frontiers in Immunology, 2026)
AimsAcute graft-versus-host disease (aGVHD) after liver transplantation (LT) is a rare but highly lethal complication, with no standardized diagnosis/treatment protocols. Our center successfully treated three patients using a comprehensive antithymocyte globulin (ATG)-based regimen. This study preliminarily evaluates the efficacy of ATG-based regimens for aGVHD, comparing outcomes with a historical cohort that received conventional treatment, to provide initial clinical evidence.MethodsThis retrospective study included three consecutive post allogeneic LT aGVHD patients treated at Tianjin First Central Hospital between January 2024 and August 2025. Their outcomes were compared with those of 10 historical controls who received conventional treatment between January 2019 and December 2023. Given the small sample size, outcomes were primarily compared descriptively and using effect size measures (odds ratio [OR]/median difference), while Fisher’s exact and Mann–Whitney U tests were performed for exploratory purposes.ResultsIn the ATG treatment group, two patients presented with fever and rash, while one presented with diarrhea; all developed skin involvement, oral ulcers, and myelosuppression, with a median posttransplant onset of 18 days (range: 15–27). Skin biopsy revealed epidermal hyperkeratosis, basal cell vacuolar degeneration, and dermal lymphocytic infiltration. Cases 2 and 3 had donor CD8+ T-cell chimerism. Median onset-to-diagnosis time was 15 days (range: 9–17). Treatment included an ATG-based regimen, tacrolimus tapering/withdrawal, low-dose glucocorticoids, intravenous immunoglobulin (IVIG), janus kinase (JAK) inhibitor (ruxolitinib), and symptomatic supportive care. All three patients achieved complete remission (CR) without serious complications, with a median diagnosis-to-remission time of 35 days (range: 17–50). In this preliminary comparison, the ATG group demonstrated a significantly higher CR rate (100% vs. 20%; p = 0.012, OR = 25.0), a lower infection rate (0% vs. 60%; p = 0.033), and a shorter median remission time (35 days vs. 62 days; p = 0.021, median difference = − 27 days) compared with historical controls.ConclusionThe diagnosis of aGVHD after LT requires integrating clinical manifestations, rash pathology, and chimerism detection. In this small series, ATG-based therapy was associated with favorable outcomes compared with a historical cohort receiving conventional therapy, suggesting that it may be a promising strategy warranting further evaluation in large-scale clinical studies.